2017
DOI: 10.1007/s00345-017-2026-4
|View full text |Cite
|
Sign up to set email alerts
|

Trends of lymphadenectomy in upper tract urothelial carcinoma (UTUC) patients treated with radical nephroureterectomy

Abstract: Although an increased trend was observed, most patients treated with RNU did not receive LND. Surgeons using a laparoscopic RNU were less likely to perform a concomitant LND, and when done, they remove less nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Zargar et al in one of the first experience on RNU already demonstrated the advantages of robotics during lymph node dissection reporting a mean value of 9.4 harvested nodes [24]. Compared to ours, also Moschini et al achieved a similar value of nodes resected during ONU and LNU [25]. Nevertheless, the number of lymph nodes yielded was reported in a low number of studies with a high heterogeneity among the studies (I 2 = 99%).…”
Section: Discussionsupporting
confidence: 40%
“…Zargar et al in one of the first experience on RNU already demonstrated the advantages of robotics during lymph node dissection reporting a mean value of 9.4 harvested nodes [24]. Compared to ours, also Moschini et al achieved a similar value of nodes resected during ONU and LNU [25]. Nevertheless, the number of lymph nodes yielded was reported in a low number of studies with a high heterogeneity among the studies (I 2 = 99%).…”
Section: Discussionsupporting
confidence: 40%
“…Consecutive patients were treated with extirpative surgery with curative intent in the form of open or laparoscopic RNU [14][15][16] for non-metastatic (N0-1 M0) high-grade UTUC between 1990 and 2016. Performance and extent of associated lymph node dissection was chosen according to surgeon or patient preference and was not standardized [17,18].…”
Section: Study Populationmentioning
confidence: 99%
“…Amongst these records, 22 were included in the qualitative synthesis, and 12 cohort studies in 14 records were included in the quantitative analysis. These studies are reported in Table 1 [5,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Five studies reported a description of their associated LND templates and these are presented in Table 2 [9, [14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Lymph node dissection (LND) can be performed in patients with suspected regional lymph node metastasis for staging purposes. A recent study investigating the trends of LND amongst UTUC patients concluded that LND is performed more regularly during open NU, these patients are also more likely to receive adequate concomitant LND when compared to those undergoing laparoscopic NU [5]. Furthermore, whether routine LND in conjunction with NU for UTUC confers any survival benefit is unknown [3].…”
Section: Introductionmentioning
confidence: 99%